Wendy Mann (FAO) talks about gaps in climate-smart agriculture implementation for Africa - CGIAR Research Program on Climate Change, Agriculture and Food Security (2014)
Wendy Mann of FAO was among delegates who attended a workshop on African Agriculture in a changing climate organized by CCAFS and partners. Here, she shares insights on African Agriculture with a focus on the CSA and the UNFCCC negotiations.